Worker wellbeing in a changing labor market - Polachek, S. W. (Research in labor economics ;, 2001)
How do workers fare in a continually changing labor market? This volume contains fifteen original scientific papers each examining how socio-economic changes affect worker wellbeing. Among the findings are: most increases in female labor force participation occur among women with high husbands' earnings, dispelling the myth that shrinking husbands' relative earnings cause women's work activities to rise; increased globalization equalizes pay between but expands pay within corporate establishments; high quality colleges widen the earnings distribution for top earners but only negligibly affect earnings for low wage earners; mathematical success depends on school quality more so than verbal learning; and adult daughters who visit ailing parents daily in a nursing home decrease their annual labor supply by about 1,000 hours implying a welfare loss of 180,000 dollars. Findings are: physical and/or sexual abuse appear to afflict over 30 per cent of the population leading to a 15 per cent drop in employment probability and a 32 per cent loss in wages; and, training workers in an entirely new occupation raises an employee's wage growth while training workers in the same occupation decreases their wage growth, at least during the Russian economy's recent transition.